Indicadores de bienestar animal en bovinos antes y durante el faenamiento, en el camal municipal de Quevedo, año 2022 - Velásquez Robles, Shirley Michelle (2022)
Animal welfare indicators in bovines were evaluated before and during slaughter, in the munici-pal slaughterhouse of Quevedo canton. Forms were designed to collect the information. To de-termine the sample size, random sampling was applied, obtaining a sample of 169 animals. The results indicate that during the investigation the entry of 369 animals from La Mana, Santo Do-mingo, Pucayacu and Valencia was registered. Upon arrival of the cattle, there were no injured or dead animals. 100% have water and waiting pens with good infrastructure conditions